Legacies, lags and long‐term trends: Effective flow restoration in a changed and changing world. (3rd October 2017) - Thompson, Ross M.; King, Alison J.; Kingsford, Richard M.; Mac Nally, Ralph; Poff, N. LeRoy
Abstract: Human impacts on natural ecosystems are pervasive and will play out more severely as human populations and per capita resource use increase. Freshwater ecosystems are critical for human well‐being and experience a diverse range of human‐induced pressures. Most river systems throughout the world have much‐altered flow regimes. The Murray–Darling Basin in southeastern Australian has been the focus of an extensive water reform process to address the over‐allocation of water for human uses. This has included many scientific investigations, hydrological modelling and the development of institutional and market structures to reallocate water. Substantial recovery of water has been achieved, which has been used to restore aspects of the natural flow regime. We reviewed recent papers on responses to flow restoration in the Murray–Darling Basin and complemented this with inferences from the global literature. Ecological responses to flow restoration are often inconsistent, site and taxon specific and difficult to detect. By combining ideas from mainstream thinking in restoration ecology with the insights from our review, we propose a conceptual model for understanding responses to flow restoration. This model incorporates key factors that influence the size of ecological responses to restoration, including existing ecological condition, legacy impacts of past change, interactions with other variables, life‐history traits of taxa and broad‐scale and long‐term trends due to climate or land‐use change.